A Framework of Rule Based Expert System for Market Basket Analysis - Weichbroth, Paweł (Architektura regułowego systemu ekspertowego do analizy koszyka zakupów, 2010)
This paper presents a novel approach to discovering association rules from market basket data. For this purpose the expert system with inference engine, visualisation engine, and knowledge base has been elaborated. After a short introduction, a general description of the system’s components is given. Then, the functionality of inference engine, visualisation engine and knowledge base is characterized briefly. The whole work is finished by conclusions and indicating future work.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 147. s. 276-291
Keywords: expert system; association rules; market basket analysis